2017
DOI: 10.1515/pubhef-2016-2114
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheitskompetenz von gesetzlich Krankenversicherten

Abstract: Zusammenfassung:In einer bundesweiten Repräsen-tativ-Umfrage zur Messung von Gesundheitskompetenz schneiden die Versicherten der Gesetzlichen Krankenversicherung gegenüber einer als Referenz herangezogenen europäischen Studie unterdurchschnittlich ab. Aus Sicht der Krankenkassen stellt das Handlungsfeld der Gesundheitskompetenz einen wichtigen Ansatz dar, um eine angemessene Nutzung des Gesundheitswesens zu erzielen und um eine Steigerung der Lebensqualität der Menschen zu erreichen. Angesichts der Ergebnisse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
1
Order By: Relevance
“…Current research on HL has shown older age, low education and migration background to be risk factors for a low HL (Adams et al, 2009;HLS-EU-Consortium, 2012;Kutner, Greenberg, Jin, Paulsen, & White, 2006;Schaeffer et al, 2016;Zok, 2017). This could not be confirmed in our sample of people with MD.…”
Section: Comparison Of Hl: Hls-md Versus Hls-germentioning
confidence: 61%
“…Current research on HL has shown older age, low education and migration background to be risk factors for a low HL (Adams et al, 2009;HLS-EU-Consortium, 2012;Kutner, Greenberg, Jin, Paulsen, & White, 2006;Schaeffer et al, 2016;Zok, 2017). This could not be confirmed in our sample of people with MD.…”
Section: Comparison Of Hl: Hls-md Versus Hls-germentioning
confidence: 61%
“…Insgesamt weisen somit 58,8 Prozent der Bevölkerung eine geringe GK auf. Im Vergleich zu den ersten Erhebungen aus den Jahren 2013 und 2014 [3,10,11] hat sie sich verschlechtert [12].…”
Section: Veränderung Der Allgemeinen Gesundheitskompetenzunclassified
“…They are all based on its concept and measuring instrument, and mainly address the general population. One study, originating in Germany, focused exclusively on statutory-insured people (Zok, 2014). The German Health Update (GEDA) conducted by the Robert Koch Institute also collected data on the health literacy of older people.…”
Section: Limited Health Literacy In Later Phases Of Lifementioning
confidence: 99%
“…Another important dimension that is regularly taken into account is age. While the research results are not always clear for the gender dimension, we know that there are (partly strong) correlations between educational status, social (and employment) status, belonging to a minority ethnic group and to an older age group on the one hand, and the average level of health literacy on the other (cf Canadian Council on Learning, 2008;WHO, 2013;Zok, 2014;Omariba and Ng, 2015;Hearian et al, 2017;Levin-Zamir et al, 2017). But little is known about the relationship of health literacy and other important dimensions of diversity.…”
Section: Concept and Measurements Of Health Literacy And The Signific...mentioning
confidence: 99%